Halal Industry and Tourism in Maros: Exploring the Harmony between Faith and Travel Values - Nusran, Muhammad; Lamatinulu; Wekke, Ismail Suwardi (Engineering And Technology Journal, 2024)
As halal tourism gains momentum, the tourist destination of Maros, Indonesia, with its predominantly Muslim population and stunning natural beauty, presents a unique opportunity. This paper explores the potential of halal tourism in Maros, exploring the benefits, challenges and main considerations for sustainable development. Analyzing Maros’ unique assets with a variety of halal-friendly attractions and government support, this paper highlights the potential of Maros and its surroundings, such as Bonto Bunga village, Moncongloe sub-district, Maros Regency, to serve Muslim tourists looking for experiences according to their religion. However, there are challenges such as standardization, human resource development and infrastructure that need to be overcome. Recommendations focus on stakeholder collaboration, community empowerment, environmental sustainability, and targeted marketing of local products. By navigating these aspects, Maros and especially Bonto Bunga village will be able to open the potential of halal tourism, contribute to economic development, foster cultural understanding, and offer satisfying travel experiences while still upholding Islamic religious values ​​and prioritizing responsible practices. answer.